Estudio comparativo de las métricas de calidad de servicio (QoS) empleando protocolos de encaminamiento reactivos DSR (dynamic source routing) y AODV (ad-hoc on demand distance vector) en redes vanets (vehicular ad-hoc networks). - Saavedra Cañar, Cristian Paul (2019)
The present work, the analysis and comparison of quality of service metrics in the reactive routing protocols is performed AODV Y DSR in network VANETs. Through the review of documentation, its characteristics, classification, applications, the different mobility models used for this type of networks, parameters for the modeling of vehicular traffic in the center of the city of Loja are studied. In order to achieved with the simulations, it was proposed that the routing nodes be implemented in a virtual way by means of the software NS-3 (Network Simulator) that is open source. Regarding mobility models, the Manhattan Grid model was chosen, which complies with the necessary characteristics for the respective simulations. The Bonnmotion tool was used to create the different scenarios where this type of networks has been deployed, which has compatibility with the previous version of the network simulator (NS-2) allowing to use this data in Ns-3 through import. Finally, to obtain the results, three scenarios with different density of nodes have been created, in which according to the recovered data it is possible to verify which is the routing protocol that best adapts to the type of Ah-Hoc networks proposed in the present work. Keywords: Ad-Hoc, AODV, Bonnmotion, Delay, DSR, Routing, Jitter, Manhattan Grid, Metrics, Mobility, NS-3, QoS, Throughput, VANET.